Empathy in Adults with Acquired Brain Injury: a Systematic Review and Meta-Analysis - Emily Clements; Kristin Naragon-Gainey; Michael Weinborn; Carmela Pestell; Dawn Neumann; David Preece; Rodrigo Becerra (Neuropsychology Review, 2026)
Empathy is the ability to recognise, share and understand others’ emotional states. Increasing evidence suggests that empathy may be impacted by acquired brain injury (ABI), with consequences for social and emotional functioning. However, the literature has been characterised by inconsistent findings and small sample sizes. To address these limitations, we provide the first meta-analytic review of empathy in adults with ABI. Specifically, the review aimed to quantify the degree of impairment in adults with ABI across four empathy-related domains: cognitive, affective, empathic concern (e.g. sympathy) and personal distress. We also sought to estimate the prevalence of deficits in each area and explore whether demographic and injury factors moderate impairment. A systematic search yielded 29 studies measuring self-reported empathy in adults with ABI versus healthy, matched peers. A series of random-effects meta-analyses revealed moderate deficits in cognitive empathy (Hedges’ g = − 0.68, 95% CI [− 0.87, − 0.50]) and affective empathy (Hedges’ g = − 0.43, 95% CI [− 0.65, − 0.21]), as well as small-to-moderate deficits in empathic concern (Hedges’ g = − 0.38, 95% CI [− 0.63, − 0.13]). No significant difference was found for personal distress. We estimated the proportion of ABI participants scoring equal to or more than 1 SD below the normative mean to be 15.3–35.0%, depending on the empathy subcomponent. Our results highlight that empathy deficits may play an important role in functional or emotional difficulties post-brain injury. This demonstrates the need for routine clinical assessment of empathy in survivors of brain injury and the need to develop interventions which target both cognitive and affective components.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Neurobiological mechanisms associated with facial affect recognition deficits after traumatic brain injury - Dawn Neumann; Brenna C. McDonald; John West; Michelle A. Keiski; Yang Wang (Brain Imaging and Behavior, 2016)

Neuroimaging and facial affect processing: implications for traumatic brain injury - Dawn Neumann; Michelle A. Keiski; Brenna C. McDonald; Yang Wang (Brain Imaging and Behavior, 2014)